A synthesis and meta-analysis of the Fe chemistry of serpentinites and serpentine minerals. (21st February 2020) - Mayhew, Lisa E.; Ellison, Eric T.
Abstract : The iron chemistry of serpentinites and serpentine group minerals is often invoked as a record of the setting and conditions of serpentinization because Fe behaviour is influenced by reaction conditions. Iron can be partitioned into a variety of secondary mineral phases and undergo variable extents of oxidation and/or reduction during serpentinization. This behaviour influences geophysical, geochemical and biological aspects of serpentinizing systems and, more broadly, earth systems. Iron chemistry of serpentinites and serpentines is frequently analysed and reported for single systems. Interpretations of the controls on, and the implications of, Fe behaviour drawn from a single system are often widely extrapolated. There is a wealth of serpentinite/serpentine chemical composition data available in the literature. Consequently, compilation of a database including potential predictors of Fe behaviour and measures of Fe chemistry enables systematic investigation of trends in Fe behaviour across a variety of systems and conditions. The database presented here contains approximately 2000 individual data points including both bulk rock and serpentine mineral geochemical data which are paired whenever possible. Measures of total Fe and Fe oxidation state, which are more limited, are compiled with characteristics of the systems from which they were sampled. Observations of trends in Fe chemistry in serpentinites and serpentines across the variety of geologic systems and parameters will aid in verifying and strengthening interpretations made on the basis of Fe chemistry. This article is part of a discussion meeting issue 'Serpentinite in the Earth system'.